2008
DOI: 10.1007/s10562-008-9785-x
|View full text |Cite
|
Sign up to set email alerts
|

Study of the Kinetics of Ammonia Synthesis and Decomposition on Iron and Cobalt Catalysts

Abstract: Activity of cobalt and iron catalysts in ammonia synthesis was determined under a pressure of 10 MPa and at the temperature range of 673-823 K, in a sixchannel integral steel reactor. The catalytic ammonia decomposition was studied in a differential reactor under the atmosphere of low concentration of ammonia (\6%) in the temperature range of 673-823 K under atmospheric pressure. The determined values of the activation energy for the ammonia synthesis reaction over cobalt and iron catalysts are 268 and 180 kJ/… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
30
0
1

Year Published

2014
2014
2020
2020

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 51 publications
(31 citation statements)
references
References 11 publications
0
30
0
1
Order By: Relevance
“…The I D /I G ratio is related to the orderliness of the graphite structure and is inversely proportional to the microcrystalline planar size, which corresponds to the in-plane dimension of a single microcrystallite in graphite [26]. According to this parameter, the degree of graphitisation of the different carbon supports follows the trend of MESO-C > Activated charcoal > MSC-30 > CNTs > Ax- 21.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The I D /I G ratio is related to the orderliness of the graphite structure and is inversely proportional to the microcrystalline planar size, which corresponds to the in-plane dimension of a single microcrystallite in graphite [26]. According to this parameter, the degree of graphitisation of the different carbon supports follows the trend of MESO-C > Activated charcoal > MSC-30 > CNTs > Ax- 21.…”
Section: Resultsmentioning
confidence: 99%
“…activity to that of Ni/CNT and Fe/CNT [20]. A recent kinetic study by Lendzion-Bielun et al [21] showed a lower ammonia decomposition activation energy on cobalt than on iron-based catalysts. Previous studies suggest that the catalytic activity of cobalt-based catalysts can be related to i. the level of dispersion and crystallite size [22] and ii.…”
Section: Introductionmentioning
confidence: 94%
“…While the ammonia molecule needs to be adsorbed on the active metal to be activated, strongly adsorbed N adatoms would, on the other hand, poison the metal active sites. Therefore, there exists an optimum nitrogen binding energy for ammonia decomposition catalysts within the range of 544-586 kJ mol -1 , with the optimum activity observed at 561 kJ mol -1 , lower than that for ammonia synthesis catalysts [27][28][29].…”
Section: Mechanism Of Ammonia Decomposition Over Heterogeneous Catalystsmentioning
confidence: 99%
“…A kinetic study by LendzionBielun et al [27]. Calculated the activation energy for NH 3 decomposition to be 27 kJ mol -1 lower on cobalt than on iron-based catalysts.…”
Section: Cobalt-based Catalystsmentioning
confidence: 99%
See 1 more Smart Citation